El papel de la Odontología en la Medicina del Sueño. - Rafael-Montalvo, Edward Frank (2025)
Dentistry contributes significantly to Sleep Medicine through the specialty known as “Sleep Dentistry” or “Dental SleepMedicine”, the importance of this specialty lies mainly in the treatment and management of sleep breathing disorders (SBD), dueto the impact of the tongue and mandibular position on the patency of the upper airway. The use of oral devices (OD) began in the20th century, with the first functional device being the so-called “monobloc”. Later, lingual retention devices, palatal elevation devices and finally mandibular advancement devices (MAD) are the main. The Clinical Practice Guideline for the Treatment of Obstructive Sleep Apnea (OSA) and Snoring with oral device was published by the American Academy of Sleep Medicine (AASM) and the American Academy of Dental Sleep Medicine (AADSM). in 2015. The main indication for OD are primary snoring and mild OSA and it could be used in patients that do not tolerate treatment with continuous positive airway pressure (CPAP). Other dental specialties also participate in the treatment and prevention of SBD, are Orthopedics and Maxillofacial Surgery. It is known that craniofacial development has a crucial impact on the size of the upper airways and any deterioration in this development will affect the size of the upper airway. Surgical treatment using orthognathic surgery, specificallymaxillomandibular advancement (MMA) surgery, has been shown to be an alternative treatment for people with OSA who cannot adhere to CPAP or OD therapy.